Evaluation of the Lundh test in the diagnosis of pancreatic disease - Levin, G. E. (1972)
The Lundh test meal was administered to 32 normal subjects and 53 patients with suspected pancreatic disease. Tryptic activity was measured in the recovered duodenal juice. The level of activity distinguished the normal subjects from those with independently confirmed pancreatic disease, particularly chronic pancreatitis and carcinoma of the pancreas. The advantages and disadvantages of the test are discussed.